The Alteration of m6A Modification at the Transcriptome-Wide Level in Human Villi During Spontaneous Abortion in the First Trimester - She, Jiajie; Tan, Kaifen; Liu, Jie; Cao, Shuo; Li, Zengguang; Peng, You; Xiao, Zhuoyu; Diao, Ruiying; Wang, Liping (Frontiers in Genetics, 2022)
A growing number of studies have demonstrated that N6 methyladenine (m6A) acts as an important role in the pathogenesis of reproductive diseases. Therefore, it is essential to profile the genome-wide m6A modifications such as in spontaneous abortion. In this study, due to the trace of human villi during early pregnancy, we performed high-throughput sequencing in villous tissues from spontaneous abortion (SA group) and controls with induced abortion (normal group) in the first trimester. Based on meRIP-seq data, 18,568 m6A peaks were identified. These m6A peaks were mainly located in the coding region near the stop codon and were mainly characterized by AUGGAC and UGGACG motif. Compared with normal group, the SA group had 2,159 significantly upregulated m6A peaks and 281 downregulated m6A peaks. Biological function analyses revealed that differential m6A-modified genes were mainly involved in the Hippo and Wnt signaling pathways. Based on the conjoint analysis of meRIP-seq and RNA-seq data, we identified thirty-five genes with differentially methylated m6A peaks and synchronously differential expression. And these genes were mainly involved in the Wnt signaling pathway, phosphatase activity regulation, protein phosphatase inhibitor activity, and transcription inhibitor activity. This study is the first to profile the transcriptome-wide m6A methylome in spontaneous abortion during early pregnancy, which provide novel insights into the pathogenesis and treatment of spontaneous abortion in the first trimester.